(Trans)forming fitness: Intersectionality as a framework for resistance and collective action - Bell, Deniece; Rahman, Saidur; Rochon, R. (Frontiers in Sports and Active Living, 2023)
Fitness is a lifelong pursuit, yet many LGBTQ2S+ 1 individuals are averse to group fitness or experiences in big box gyms. Due to the COVID-19 pandemic, virtual fitness programs offered the potential to facilitate opportunities for the greater inclusion of such individuals and the chance to connect, collaborate and advocate for a change in who and what defines fitness. Justice Roe, owner of Fit4AllBodies, utilizes the term fitness industrial complex to provide a framework to discuss the problems of exclusion. His explanation supports research documenting that bodies that are not “the norm”, defined by ableism, classism, (hetero)patriarchy and racism, fueled by white supremacy, are oftentimes viewed as “less than” in the fitness and recreation world ( 1– 3). Applying an intersectional framework, this article explores the possibilities for transformative collective action in fitness communities that removes barriers and challenges the injustices that contribute to racialized LGBTQ2S+ individuals feeling unwelcome. With the need to shift to virtual training spaces as a result of a global pandemic, and the rise in the public discourse surrounding racial injustices both on and offline, a sense of belonging and community is important, especially among groups that often face exclusionary practices, such as racialized LGBTQ2S+ community members. These individuals are at greater risk of losing opportunities to access fitness programs that can provide immense health and psychological benefits. What could an intersectional perspective on resistance in sport look like? Using the example of LGBTQ2S+ access to online fitness spaces during the prolonged global COVID-19 pandemic starting in 2020, we suggest that explicit coaching education and intentional communities, centered around social justice, are needed to address the historical roots of systemic oppression, accessibility, and social constructs tied to fitness.